Some manifestations of the theme of Childhood in poems by Charles Baudelaire and Manoel de Barros - Sales, Janaina Jenifer de [UNESP] (Univ Studi Bologna, Almadl Journals, 2022)
Although belonging to two distinct universes, such as the poems of Manoel de Barros, and Charles Baudelaire, they touch each other when they bring the theme of childhood to their work. In almost all of Barros' work, it is observed that childhood takes control of language. Whereas in Baudelaire, it is about a child who makes up the landscape of the oppressed. This article intends to lead us to reflect on the place of children in Western societies, especially in French literature in the 19th century and in Brazilian literature in the 20th century.
Keywords: Brazilian poetry; French poetry; Manoel de Barros; Charles Baudelaire; Comparative literature